Parameterized unit tests with unit meister. - Tillmann, Nikolai (Software engineering notes.)
Parameterized unit tests extend the current industry practice of using closed unit tests defined as parameterless methods. Traditional closed unit tests are re-obtained by instantiating the parameterized unit tests. We have developed the prototype tool Unit Meister, which uses symbolic execution and constraint solving to automatically compute a minimal set of inputs that exercise a parameterized unit test given certain coverage criteria. In addition, the parameterized unit tests can be used as symbolic summaries during symbolic execution, which allows our approach to scale for arbitrary abstraction levels. Unit Meister has a command-line interface, and is also integrated into Visual Studio 2005 Team System.